Diversity and equity: dealing with biological and social differences - Friedhelm Nachreiner (Universidade de São Paulo, 2004)
In the context of the design of working hours inequities in health associated with biological, psychological, social, and socioeconomic diversities can be observed. The paper first tries to set up a frame of reference for a discussion of this topic, relating to the Universal Declaration of Human Rights and some recent discussions on equity in health and then goes into some factors that produce inequities in health in the context of the design of working hours, dealing with sex or gender, age and job age, personality traits, marital status, social support, diversities in values, and socio-economic differences; the discussion deals with approaches on how to deal with these differences and inequities. No contexto do planejamento das horas de trabalho, observam-se iniqüidades na saúde associadas à diversidade biológica, psicológica, social e socioeconômica. Inicialmente, procura-se criar uma estrutura de referência para a discussão do assunto, relacionando-o à Declaração Universal dos Direitos Humanos e a discussões recentes sobre eqüidade em saúde. Em seguida, passa-se a alguns fatores que causam iniqüidades em saúde no contexto do planejamento das horas de trabalho, associados ao sexo ou gênero, idade e tempo de permanência no serviço, características de personalidade, estado civil, apoio social, diversidades de valores e diferenças socioeconômicas; a discussão estende-se sobre enfoques para lidar com estas diferenças e iniqüidades.